(untitled) (Bangladesh Journal of Anatomy, 2015)
Context: Human hand is one of the most studied subjects in modern science and evolutionary biology. By virtue of evolution and genetically arrangements, digital lengths vary from person to person according to age, sex, races, occupation or even environmental influences. It has been found that the digital lengths and their ratios are not the same in different sexes or even both hands. Specially, index to ring digit lengths and their ratios which already have been proved to represent sexual dimorphism may differ in both hands of an individual. Many studies among different races have shown that index to ring digit ratio (2D:4D) 31 among female and <1.00 among male. In this study, this variation of the index finger (2D) and ring finger (4D) length and their ratio (2D:4D) has been analyzed and compared in both hands among the adult male Bangladeshis. Materials & Methods: A Cross sectional analytical study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka, from July 2012 to June 2013. The study was performed on 100 male MBBS students (20-25 years of age) of Dhaka Medical College, Dhaka. With the help of digital vernier caliper measurements of digital lengths were recorded. Paired t- test was done for statistical analysis of the results. Results: Significant difference has been found in the lengths of index finger (2D) and ring (4D) digits and their ratios (2D:4D) between both hands where left index finger (L2D) length was higher than right index finger (R2D) length (P<0.05) and the length of right ring finger (R4D) was significantly greater (P<0.001) than left ring finger (L4D). The right index to ring digit ratio (R2D:4D) was significantly less than left index to ring digit ratio (L2D:4D) in male (P<0.001) that indicated sexual dimorphism in 2D:4D ratio is more prominent in the right hand in male. Also, right index to ring digit ratio (R2D:4D) was recorded <1.00 in 86% and 31 in 14% subjects and left index to ring digit ratio (L2D:4D) was recorded <1.00 in 76% and 31 in 24% of subjects. Conclusion: Digital lengths especially index (2D) and ring (4D) digit lengths are often use to determine sexual dimorphism. Also, study over the variations of digital lengths have great medicolegal importance to determine age, sex and race of an individual. Bangladesh Journal of Anatomy July 2015, Vol. 13, No. 2, pp. 57-61